Aplicação da otimização por enxame de partículas com topologia "multi-ring" na estimação de parâmetros de linhas de transmissão - Arruda, Sérgio Alexandre Martins (2015)
Present world demands high availability of electricity for various equipment, in a context in which dominates the intensive use of technology. The electricity is transported from generation centers to consumers through Transmission Lines (TLs), which in Brazil have significant dimensions, given the continental size of the country, his predominantly hydro power plant generation, located long distances from major centers consumption. To ensure compliance of this high demand, often the electric power companies overload these TLs, generating undesirable effects, such as the formation of arrow in the conductors, for example. Monitoring of TL operating conditions is key part, therefore, to ensure system availability and security. This work aims in this context to present a method to assist in the monitoring of three-phase TLs of simple circuit based on measurement of electric and magnetic fields of the line and in application of an optimization procedure based on Particle Swarm Optimization metaheuristic, with a topology denominated Multi-Ring, to estimate simultaneously the values of current, voltage, cable-ground clearance of conductors and distance between phases, in a cross section of the line, assisting electric power companies and the National Electric System Operator (ONS) in the monitoring task. The good results achieved, combined with its simplicity of implementation compared to other methods and its robustness, indicate their suitability for estimating these parameters. Associated with this, the reasonably low times obtained in the execution make it promising for use by the electric power company and by the system operator as an auxiliary tool in monitoring TLs.